The QFHSA Supports Bill S-251 : An Act to Repeal Section 43 of the Criminal Code (Truth and Reconcilliation Commission of Canada's Call to Action Number 6) - Quebec Federation of Home and School Associations (QFHSA) (2023)

Faits saillants : Enquête sur la vulnérabilité des pères d'expression anglaise - Community Health and Social Services Network (CHSSN) (2022)

Survey Highlights on the Vulnerability of English-speaking Fathers - Community Health and Social Services Network (CHSSN) (2022)

Brief Addressed to the Committee on Culture and Education and Bill 56 : An Act to Prevent and Deal with Bullying and Violence in Schools - Quebec Federation of Home and School Associations (QFHSA) (2012)
The Quebec Federation of Home and School Associations (QFHSA) welcomes the opportunity to comment on Bill 56, An Act to prevent and deal with bullying and violence in schools.

Un mémoire à l'intention de la Commission de la culture et de l’éducation : portant sur le projet de loi no 56 : Loi visant à lutter contre l’intimidation et la violence à l’école - Quebec Federation of Home and School Associations (QFHSA) (2012)
La Fédération Québécoise des Associations Foyers-Écoles (FQAFÉ) accueille l’opportunité de pouvoir commenter le projet de loi 56, intitulé Loi visant à lutter contre l’intimidation et la violence à l’école.

Open and Public Inquiry into the Death of Mr. Rohan Wilson - Alliance Quebec (AQ) (2004)

"Hate is Hate" - Alliance Quebec (AQ) (2003)

Press Conference - Alliance Quebec (AQ) (2002)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)